Religious Tolerance in Multicultural Communities: Towards a Comprehensive Approach in Handling Social Conflict - Suradi, Ahmad; Kenedi, John; Surahman, Buyung (Udayana Journal of Law and Culture, 2020)
This article is aimed to analyze the need for handling social conflict through the planting of tolerance values in multicultural societies that in line with statutory provisions . It is a socio-religious study that, to some extent, applies a legal approach. A library study was conducted by collecting data and information from text books, scientific journals, website contents. The legal analysis was based on principles and norms contained in legislation and regulations. It applies Miles and Huberman's interactive analysis model which includes data reduction, data presentation, and conclusion. The study suggested that planting tolerance values ?? is a grand and noble concept that would become an organic part of Indonesia . Tolerance is function ed as a guardian, safeguard, peace-maker, and unifier communication and interaction to realize good relations between community members . Besides, the law on handling of social conflict has covered the mechanism to address this matter by means of c onflict p revention, c essation of c onflicts, and p ost- c onflict r ecovery .